(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
In modern language education, reading is no longer viewed as a passive act of decoding words and extracting basic information. It is increasingly understood as an interactive and reflective process in which learners construct meaning, evaluate arguments, and connect textual ideas with prior knowledge. This article examines the role of critical thinking in improving reading comprehension in English as a Foreign Language (EFL) contexts. It argues that the integration of critical thinking strategies into reading lessons helps learners move beyond literal understanding toward analysis, inference, evaluation, and interpretation. The study is based on a theoretical analysis of major works on critical thinking, critical reading, Bloom’s revised taxonomy, and scaffolding, as well as recent empirical studies conducted in EFL classrooms.